Method and engineering tools for in-vehicle information systems (In-Vehicle Information Systems), focusing on the risk of driver distraction - Carvajal, Carlos (2022)
Thousands of deaths a year are attributed to driver distractions while driving. The automotive industry has worked for decades maturing development guidelines and complex evaluation scenarios for the acceptance of infotainment centers as an integral part of the vehicle. The massification of smart wearable devices with a gigantic ecosystem of mobile applications not designed for the particularities of the automotive environment, easily bypasses the precautions of safe driving schemes. There is then, a niche of developers without the formal knowledge and economic support to adequately enter the automotive applications development. Cost-benefit methods and tools accessible in the context of software engineering are proposed to support the development of in-vehicle information systems in accordance with the requirements of current regulations and standards.